First report of Epicoccum nigrum causing disease in Lotus corniculatus in Argentina - Colavolpe, Maria Belen (2018)
The genus Epicoccum was reported in Argentina as a seed pathogen in Lotus spp. (Sisterna & Lori, 2005). The isolate in the current study had 98% identity with E. nigrum (KC568289 and KY303832) that caused leaf spot in Lablab purpureus and brown leaf spot in loquat, respectively (Mahadevakumar et al., 2014; Wu et al., 2017). To our knowledge, this is the first report of E. nigrum causing leaf spot in L. corniculatus in Argentina.